The Drivers of Tobacco Cultivation in Jhenaidah: An Anthropological Exploration of Farmer Motivations - Razu, Ashif Hasan (Journal of Sustainability and Environmental Management, 2024)
This study investigates the factors driving tobacco cultivation in Jhenaidah, Bangladesh, focusing on the motivations of farmers in the region. The study examines Dangipara village in Shailkupa Upazila, a key tobacco production site. This study explores the reasons behind farmers' continued engagement in tobacco farming despite its well-documented environmental and health impacts. Employing qualitative methods, including ethnographic interviews and focus group discussions with 40 experienced farmers, the study identifies key drivers such as the availability of modern agricultural tools, access to microcredit, and the influence of tobacco companies in shaping farming practices. The findings reveal that tobacco farming is favored due to its higher profitability, stable market conditions, and strong support from tobacco companies when compared to traditional crops such as paddy, pulses, and vegetables, which are often hindered by price instability and inadequate marketing infrastructure. Additionally, the study highlights the importance of required family labor, as households with more working members benefit from reduced cultivation costs. Favorable land conditions also play a role, as long-term tobacco farming has degraded soil quality, making it unsuitable for alternative crops. The latent role of the Agriculture Office is another factor, as the lack of effective support for alternative crops contrasts with the active assistance provided by tobacco companies.  Lastly, influence from neighbors who have successfully adopted tobacco farming encourages others to follow suit, despite the challenges faced by less affluent farmers.  Based on these findings, the study recommends addressing market challenges and promoting alternative, profitable crops to incentivize farmers to transition away from tobacco cultivation, thereby reducing the region's dependence on tobacco farming.